The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/pathogens11121531
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the COVID-19: Persistence, Effectiveness, and Immune Escape of the Neutralizing Antibody in Convalescent Serum

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), a new coronavirus causing Coronavirus Disease 2019 (COVID-19), is a major topic of global human health concern. The Delta and Omicron variants have caused alarming responses worldwide due to their high transmission rates and a number of mutations. During a one-year follow-up (from June 2020 to June 2021), we included 114 patients with SARS-CoV-2 infection to study the long-term dynamics and the correlative factors of neutralizing antibodies (NAbs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Several study studies reported that the elderly showed lower neutralization potency against the prototype and other VOCs (including B.1.1.7, B.1.351 and P.1.) than the younger individuals after one, two or three doses of vaccines ( Collier et al., 2021 ; Kawasuji et al., 2021 ; Liang et al., 2022 ; Newman et al., 2022 ; Tuekprakhon et al., 2022 ; Xu et al., 2021 ). The poor neutralizing responses, including lower levels of antibodies (quantity) and lower-affinity antibodies (quality), in the elderly individuals might be explained by reduced T-cell response ( Tober-Lau et al., 2021 ), lowered spike-specific IgG + IgM − CD19 + memory B cells, decreased somatic hypermutation in the BCR gene, or less enrichment for public BCR clonotypes associated with neutralization ( Collier et al., 2021 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several study studies reported that the elderly showed lower neutralization potency against the prototype and other VOCs (including B.1.1.7, B.1.351 and P.1.) than the younger individuals after one, two or three doses of vaccines ( Collier et al., 2021 ; Kawasuji et al., 2021 ; Liang et al., 2022 ; Newman et al., 2022 ; Tuekprakhon et al., 2022 ; Xu et al., 2021 ). The poor neutralizing responses, including lower levels of antibodies (quantity) and lower-affinity antibodies (quality), in the elderly individuals might be explained by reduced T-cell response ( Tober-Lau et al., 2021 ), lowered spike-specific IgG + IgM − CD19 + memory B cells, decreased somatic hypermutation in the BCR gene, or less enrichment for public BCR clonotypes associated with neutralization ( Collier et al., 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…The Omicron BA.4/5 variants have new mutations in their RBD, such as R493Q, L452R and F486V, indicating possible evolution from BA.2 ( Liang et al., 2022 ). In this study, BA.4/5 variants had 6.10-fold reduced neutralization in CLD patients and 5.11-fold in HCs when compared with the prototype, consistent with the result of a previous mRNA booster vaccination cohort ( Tuekprakhon et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…And after 40 years old, it shows a trend of sharp decline [35] . Besides, there was a study showed that in Omicron patients, young people had higher levels of neutralizing antibodies [36] . The above differences may allow the virus in young patients to be cleared faster without significantly affecting the immune system, so that the lymphocyte count is still within the normal range, and the clinical symptoms of young patients are relatively mild compared to the elderly [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specific anti-H1N1 virus drugs can quickly inhibit the virus, so that H1N1 virus can be quickly cleared in vivo. However, Omicron often has immune escape due to its strong mutation ability [45] , and the ability of neutralizing antibodies produced by the body to Omicron strain is significantly reduced [36] . Besides, the antiviral effect of Omicron is limited, which leads to a significant prolongation of virus clearance time.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of T cells, which play an important role in viral elimination ( Kumar et al., 2018 ), gradually decreases and shows a sharp decline after age 40 years ( Simnica et al., 2019 ). One study showed that in patients with Omicron, younger people had higher levels of neutralizing antibodies ( Liang et al., 2022 ). These differences may allow faster and more efficient viral clearing in younger patients, without significantly affecting the immune system, so that their lymphocyte counts remain within the normal range; this is supported by evidence that clinical symptoms among younger patients are relatively mild compared with those of older adults ( Davies et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%